Open wide : a novel - Gross, Jessica (Abrams Press, 2025)
"Olive is desperate to get close to Theo - really,really close. She's always struggled to connect with people. And how she's in her thirtiies, single, and so flustered by relationships that she secretly records her conversations, hoping to decipher social cues and find a way to be less alone. Then Theo turns up for a shift at the same food pantry where she volunteers. He's a surgeon fascinated by human organs, a former soccer player, and possibly as weird as Olive. For the first time, someone seems to crave and understand her. Every recording of Theo is a balm, which just makes Olive more afraid of losing him. The only solution seems to be to bind him to her forever. Luckily, the gap between Theo's front teeth is just wide enough for something--or someone--to slip inside. Arresting and immersive, Open Wide explores the complexities of intimacy, love and consent, as universal human impulses bleed into the surreal"--Back cover.